Parapharyngodon hispidus n. sp. (Nematoda: Pharyngodonidae) in Tropidurus hispidus (Spix) (Squamata: Tropiduridae) from Caatinga Biome of the Vale do São Francisco, state of Pernambuco, Brazil with a key for the Neotropical species of the genus Parapharyngodon Chatterji - Ferreira, Antonio Carlos Santos; Vieira, Fabiano Matos; Da Silva, Diego César Nunes; Ribeiro, Leonardo Barros; Ferreira, Jayelen Alves; Muniz-Pereira, Luís Cláudio (Zootaxa, 2021)
One species of Parapharyngodon Chatterji (Nematoda: Pharyngodonidae), parasitizing the large intestine of Tropidurus hispidus (Spix) (Squamata: Tropiduridae) in Caatinga biome from Brazil is described and illustrated . This new species differs from a part of its congeners by a set of characters in males: the presence of four pairs of caudal papillae, unpaired post cloacal papilla absent, and smooth anterior cloacal lip. Among the Parapharyngodon species with four pairs caudal papillae, unpaired post clocal papilla absent, and smooth cloacal lips, only P. hispidus n. sp. and P. jairaipurii Rizvi & Bursey (Oriental realm), features the same characteristics including sharp pointed tip of spicule, stout terminus or spike of tail of females, and punctate ornamentation of the eggshell. However, these two species are different by the size of spicules (spicules of P. jairaipuri are around 55% of the size spicules of P. hispidus n. sp.); and the arrangement of the caudal papillae (two pairs of adcloacal papillae in P. jaraipuri which are absent in P. hispidus n. sp.). Parapharyngodon hispidus n. sp. is the 55th species assigned to the genus and the 11th species of this genus described in Neotropical hosts.